MORPHOLOGICAL, ANATOMICAL AND CYTOLOGICAL INVESTIGATIONS ON THREE TAXA OF CENTAUREA L. (ASTERACEAE) FROM TURKEY - Tasar, Neslihan; dogan, Gulden; Kiran, Yasar; Rahman, M. Oliur; Cakilcioglu, Ugur (Bangladesh Assoc Plant Taxonomists, 2018)
Morphological, anatomical and cytological features of three Turkish taxa of Centaurea L., viz. C. polypodiifolia Boiss. var. polypodiifolia, C. urvillei DC. subsp. urvillei and C. urvillei subsp. armata Wagenitz were investigated. Stem anatomy revealed the presence of a thick cuticle layer outside the stem, and epidermis with dense hairs was observed in the lower part. Investigation on leaf anatomy showed that different types of hairs on the outside of the leaf were very intense. Palisade parenchyma was observed below the upper and lower epidermis. In Centaurea polypodiifolia var. polypodiifolia, chromosome number was found to be 2n=16, while in C. urvillei subsp. urvillei and C. urvillei subsp. armata 2n=20. Total karyotype length of C. polypodiifolia var. polypodiifolia, C. urvillei subsp. urvillei and C. urvillei subsp. armata was 22.9 mu m, 37.84 mu m and 40.01 mu m, respectively. Among the investigated taxa the karyotype asymmetry index was found lowest in C. urvillei subsp. armata. Satellite was detected in C. urvillei subsp. urvillei and subsp. armata, while it was absent in C. polypodiifolia Boiss. var. polypodiifolia.
Keywords: Centaurea; Anatomy; Cytology; Taxonomy; Asteraceae; Turkey